Time‐Resolved Grazing Incidence X‐Ray Absorption Spectroscopy for the In Situ Investigation of the Initial Stages of Sputter‐Deposited Copper Thin Films. Issue 9 (13th October 2021) - Lützenkirchen-Hecht, Dirk; Stötzel, Jan; Just, Justus; Müller, Oliver; Bornmann, Benjamin; Frahm, Ronald
Abstract : The sputter deposition and the growth of thin copper films on float glass substrates are in situ studied using grazing incidence, reflection mode X‐ray absorption fine structure spectroscopy with subsecond time resolution. The experimental data are compared with model calculations, assuming the presence of crystalline, face‐centered cubic metallic Cu nanostructures. From a detailed analysis of the measured spectra, the film thickness as well as the surface roughness is determined, leading to a detailed understanding of the films growth as a function of the sputter deposition time. In particular, different stages of film growth can clearly be distinguished from the fits of the experimental data. The results suggest the formation of isolated, approximately nm‐sized copper clusters in the initial phase of the film deposition for the first few seconds, a coalescence phase with a nominal thickness of ≈1.5−2.8 nm, constant roughness of about 1.4 nm for the subsequent ≈5 s, and finally 3D growth of the Cu crystallites in the film for later stages of film growth. Further prospects of the methodology are given. Abstract : A detailed analysis of time‐resolved, grazing incidence X‐ray absorption spectroscopy data provides access to the dynamics of structure formation during thin film growth by sputtering. For Cu thin films, nanometer‐sized clusters appear during the first few seconds, coalescence is subsequently observed for about 5 s, and 3D growth of copper occurs for films of about 3 nm thickness and more.